Investigations on Wear Behavior of Aluminium Composites at Elevated Temperature - B. R. Senthil Kumar; G. Gopalarama Subramaniyan; N. Pragadish; P. M. Venkatesh; Soni Sanjay; C. M. Velu; G. Navaneethakrishnan; Suresh Vellingiri; Venkatesan Govindarajan (Advances in Materials Science and Engineering)
The aerospace aluminium alloy AA7050 was reinforced with Al2O3 of average particle size 5 m in this study using the stir casting method. To eliminate surface imperfections, AA7050/Al2O3 composites with varied weight percentages (0, 2, 4, 6) were manufactured, and wear tests on composites were carried out utilizing a pin-on-disc apparatus that varied load, velocity, temperature, and weight %. The tensile and hardness tests were carried out at a high temperature. The inclusion of particles enhances wear resistance by establishing a mechanically mixed layer (MML), according to the findings. The wear resistance at 300°C was 100% higher in comparison with resistance at 150°C. Because of the Orowan strengthening and Hall–Petch effect, the tensile strength and hardness of composites enhanced. Temperature, tracked by the weight % of strengthening powders, was the most important factor that influences the wear resistance of the composites. The findings showed that the material properties of AA7050/4wt%Al2O3 at 150°C and AA7050/2wt%Al2O3 at 300°C are superior than base alloy.